How does hybrid environmental governance work? Examining water rights trading in China (2000–2019). (15th June 2021) - Svensson, Jesper; Wang, Yahua; Garrick, Dustin; Dai, Xiaoping
Abstract: Intensifying competition for water induces the growth of water markets in several countries for sharing water between rural communities and cities. While there is a growing recognition that adoption of market mechanisms in environmental governance relies on the state and different institutional arrangements, much less is known about how the interconnections among the state, market-tools, and the community work in practice. In China's distinctive political system, the central government has adopted a 'Two-Hands' approach (两手发力) to water governance – a combination of strong central regulation and infrastructure development on the one hand, and adoption of market principles on the other to improve water reallocation. A recent study has explored the policy evolution underpinning this transition. However, no studies have systematically examined the implementation of the Two-Hands approach to reveal the underlying institutional hybrid patterns in environmental governance. This study fills this research gap by employing a Fuzzy Set Qualitative Comparative Analysis (fsQCA) to analyze how the interplay of the central government, market, and local governance shapes water rights trading patterns. A total of 29 water-scarce cities using water rights trading with 385 transactions were investigated for the period between 2000 and 2019 by combining evidence from fsQCA and qualitative case-studies. The implications drawn from interpreting the results are as follows: (1) the central government shapes the development of the market and its transactions but this is expressed in multiple ways through pilot projects and the national water exchange platform; (2) establishing water markets and investing in water infrastructure are mutually reinforcing, rather than mutually exclusive; and (3) local governments employ different property rights arrangements to adapt water markets in China's centralized politically institutional context. Highlights: Pilot programs and market platforms tied to the central government lead to the most water rights trading at the local level. The central and local governments are investing in physical infrastructure to enable the development of water markets. Unique cases illustrate how farmer associations, markets, and local governments are forcing the hybridization of governance. Future studies should more carefully examine exclusion and boundary rules in Chinese water markets.